2005
DOI: 10.1007/s11882-005-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of grass pollen allergens

Abstract: Among pollen allergens, grass pollen allergens are some of the most frequent contributors to allergic symptoms. Substantial progress has been made since the 1960s in the identification and characterization of the grass allergens. Members of this group belong to the Poaceae family, and have been classified into 13 distinct groups based on their structure, and their biological and immunologic properties. The major contributors to allergy and, hence, most studied among the grass allergens, are those belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 36 publications
2
38
0
2
Order By: Relevance
“…In contrast, the GI extract, which showed less than 50% inhibition for Lm immunodominant components, presents in its composition grass pollen tribes (Triticeae and Aveneae) phylogenetically different from L. multiflorum (Poeae). Altogether, these results are consistent with inhibition radioimmunoassay and ELISA studies, using crude extracts of grass pollen of the family Poaceae that showed strong cross-reactivity between their members (1,10,36). Further inhibition experiments should be conducted with purified or recombinant major allergens to confirm the grouping of the individual allergens.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, the GI extract, which showed less than 50% inhibition for Lm immunodominant components, presents in its composition grass pollen tribes (Triticeae and Aveneae) phylogenetically different from L. multiflorum (Poeae). Altogether, these results are consistent with inhibition radioimmunoassay and ELISA studies, using crude extracts of grass pollen of the family Poaceae that showed strong cross-reactivity between their members (1,10,36). Further inhibition experiments should be conducted with purified or recombinant major allergens to confirm the grouping of the individual allergens.…”
Section: Discussionsupporting
confidence: 83%
“…Pollen allergens from groups 1 and 5 are highly conserved in most clinically relevant grasses (33)(34)(35)(36) and proved to be important in this study. However, the 28-30-and 32-35-kDa components likely related to allergens from groups 5 and 1, respectively, showed more than 50% inhibition with the Lp and GII extracts, and less than 50% inhibition when the GI extract was used.…”
Section: Discussionmentioning
confidence: 70%
“…The few published studies of clinical thresholds for Poaceae pollen have been conducted in Europe, where grass species with the C3 photosynthetic pathway dominate. Investigations of protein allergens from tropical grasses, or indeed other tropical plant families, are an acknowledged gap in the available literature (Mohapatra et al, 2005;Radauer and Breiteneder, 2006). The majority of allergenic grass species characterized thus far belong to the Pooideae sub-family which has the C3 photosynthetic pathway, yet on a global scale, about one-half of all known grass species belong to a tropical functional group with the C4 photosynthetic pathway (Gaut, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Pollen grains of ragweed of Ambrosia species (6) and grasses of the Poaceae family, such as timothy (Phleum pratense), rye (Lolium spp. ), Kentucky blue grass (Poa pratensis), orchard grass (Dactylis glomerata), Bermuda grass (Cynodon dactylon), and others (7), are also among the most clinically relevant sources of allergens.…”
mentioning
confidence: 99%